Cerebrospinal Fluid Pressure Reduction Results in Dynamic Changes in Optic Nerve Angle on Magnetic Resonance Imaging. Issue 1 (March 2019) - Hu, Ranliang; Holbrook, John; Newman, Nancy J.; Biousse, Valerie; Bruce, Beau B.; Qiu, Deqiang; Oshinski, John; Saindane, Amit M.
Abstract : Background: Optic nerve sheath tortuosity is a previously reported, but incompletely characterized, finding in idiopathic intracranial hypertension (IIH). We hypothesized that optic nerve angle (ONA), as a quantitative measure of tortuosity, would change dynamically with cerebrospinal fluid (CSF) pressure status of patients with IIH immediately before and after lumbar puncture (LP). Methods: Consecutive patients with suspected IIH referred for MRI and diagnostic LP were prospectively enrolled in this single institution, institutional review board–approved study. Each patient underwent a pre-LP MRI, diagnostic LP with opening pressure (OP) and closing pressure (CP), and then post-LP MRI all within 1 session. Sagittal and axial ONAs were measured on multiplanar T2 SPACE images by 2 neuroradiologists on pre- and post-LP MRI. Effects of measured pressure and CSF volume removal on changes in ONA were analyzed as was interrater reliability for ONA measurement. Results: Ten patients with IIH were included {all female, median age 29 (interquartile range [IQR] 25–32)}. All patients had elevated OP (median 37, IQR 34–41 cm H2 O), and significantly reduced CP (median 18, IQR 16–19 cm H2 O, P < 0.001) after CSF removal (IQR 13–16 mL). Within patients, mean ONAs (sagittal and axial) were significantly lower before (162 ± 9°, 163 ± 10°) than after (168 ± 7°, 169 ± 5°) LP ( P = 0.001, 0.008, respectively). Interrater reliability was higher with sagittal ONA measurements (0.89) than axial (0.72). Conclusions: ONA changes with short-term CSF pressure reduction in patients with IIH, establishing optic nerve tortuosity as a dynamic process related to CSF status.